Association of advance care planning with place of death and utilisation of life-sustaining treatments in deceased patients at Taipei City Hospital in Taiwan. Issue Volume 12:Issue e3(2022) (28th October 2020) - Yen, Yung-Feng; Lee, Ya-Ling; Hu, Hsiao-Yun; Sun, Wen-Jung; Ko, Ming-Chung; Chang, Shen-Shong; Chen, Chu-Chieh; Huang, Sheng-Jean; Chu, Dachen
Abstract : Objective: Evidence is mixed regarding the impact of advance care planning (ACP) on place of death. This cohort study investigated the effect of ACP programmes on place of death and utilisation of life-sustaining treatments for patients during end-of-life (EOL) care. Methods: This prospective cohort study identified deceased patients between 2015 and 2016 at Taipei City Hospital. ACP was determined by patients' medical records and defined as a process to discuss patients' preferences with respect to EOL treatments and place of death. Place of death included hospital or home death. Stepwise logistic regression determined the association of ACP with place of death and utilisation of life-sustaining treatments during EOL care. Results: Of the 3196 deceased patients, the overall mean age was 78.6 years, and 46.5% of the subjects had an ACP communication with healthcare providers before death. During the study follow-up period, 166 individuals died at home, including 98 (6.59%) patients with ACP and 68 (3.98%) patients without ACP. After adjusting for sociodemographic factors and comorbidities, patients with ACP were more likely to die at home during EOL care (adjusted OR (AOR)=1.71, 95% CI 1.24 to 2.35). Moreover, patients with ACP were less likely to receive cardiopulmonary resuscitation (AOR 0.36, 95% CI 0.25 to 0.51) as well as intubation and mechanical ventilation support (AOR 0.54, 95% CI 0.44 to 0.67) during the last 3 months of life. Conclusion: Patients with ACP were more likely to die at home and less likely to receive life-sustaining treatments during EOL care.